The sustainability of communicative packaging concepts in the food supply chain. A case study part 1. Life cycle assessment. - Dobon, Antonio
Purpose In recent years, a new perspective for food packaging has emerged as a result of several issues like quality, safety, competitive prices or providing of useful information to consumers. This new perspective is called communicative packaging. Communicative packaging may influence consumers/companies on purchasing decisions. Since the environmental evaluation of such systems has not yet been performed, this paper is focused on the environmental evaluation of a flexible best before data (FBBD) communicative device on a packaging consumer unit and its implications on reducing environmental impacts related to fresh products. This consumer unit consists of a nanoclay based polylactic acid tray filled with pork chops. Methods The environmental assessment of the consumer unit was made through life cycle assessment (LCA) using a cradle to gate approach. Environmental impacts were assessed according to the Eco-Indicator 99 v2.1 methodology in Individualist (1) perspective. Results and discussion Several results were obtained from the LCA. With regard to environmental impacts of the FBBD, most of them were due to the paper substrate used for the manufacture of this communicative packaging concept as well as to the transports for delivering the components of the FBBD communicative device. On the other hand, when environmental impacts of packaging system with and without FBBD were compared, a large environmental load was detected for the system that has the communicative device affixed as a result of the higher weight of the package. However, the environmental load caused by the use of the FBBD was minimal in comparison with the total environmental load of the whole packaging system. On the contrary, the consumer unit that has the communicative device affixed showed less environmental burden than the consumer unit that has not affixed the device. This was due to the environmental benefits that the communicative device provides by reducing the amount of out of date packaged products at retailer outlets. Conclusions The use of a FBBD contributes to minimize environmental burdens related to the production, packaging and delivery of pork chops since it facilitates a dynamic control of out of date products even though the consumer unit with FBBD weighs 1 g more than the consumer unit that does not use the communicative device. Recommendations The results presented in this paper are estimated results of a specific case study for a prototype of communicative packaging device. Consequently, these results must be considered as a first approach according to future developments on communicative packaging.
Keywords: Communicative packaging; Life cycle assessment; Packaging; Sustainability